Solid self-microemulsifying drug delivery systems in modern pharmaceutics: design, characterization, and clinical applications - P. R. Kaple; S. S. Agarwal (Journal of Applied Pharmaceutical Research, 2026)
Background: Approximately 40% of marketed medicines and 70% of pipeline products exhibit poor aqueous solubility, leading to inconsistent oral bioavailability and impaired efficacy. S-SMEDDS represent a revolutionary approach for converting liquids into stable solid dosage forms. Methodology: Methods employed to prepare S-SMEDDs include adsorption onto carriers, spray drying, hot-melt extrusion, and freeze-drying. Characterization includes assessing self-emulsifying behavior, dynamic light scattering, powder diffraction, and thermal analysis. Results and Discussion: Depending on the drug's characteristics, the formulation composition, and the study conditions, S-SMEDDS can increase bioavailability by two to ten times. However, for some extremely lipophilic BCS Class II and IV pharmaceuticals, significantly greater benefits (up to ~50-fold) have been documented. Several investigations have demonstrated that S-SMEDDS exhibit better physical and chemical stability than liquid systems under ICH Q1A(R2) accelerated storage conditions due to reduced lipid mobility and a lower risk of phase separation. Applications extend to the treatment of cardiovascular, oncological, and endocrine disorders with improved pharmacodynamic efficacy. The multiple absorption mechanisms in S-SMEDDS include improved solubilization, reduced precipitation, lymphotropic delivery, and inhibition of efflux pumps. They demonstrate higher chemical and physical stability, precise dosing, and better patient adherence when compared to traditional liquid counterparts. Conclusion: S-SMEDDS constitute an established pharmaceutical platform that overcomes the drawbacks associated with liquid lipid drug delivery systems. Their high effectiveness, manufacturability, and compatibility with novel technologies such as three-dimensional printing and artificial intelligence position them to be the foundation for precision oral drug delivery.